2019
DOI: 10.1037/sah0000133
|View full text |Cite
|
Sign up to set email alerts
|

HIV-stigma, self-compassion, and psychological well-being among gay men living with HIV.

Abstract: Gay men living with HIV (MLWH) are often adversely affected by stigma related to both their serostatus and their sexual orientation, and the experience of living with HIV appears to increase feelings of internalized homophobia (IH). Little research attention has focused, however, on factors that may buffer the impact of HIV-stigma and IH on well-being among men living with HIV. Self-compassion, which consists of self-kindness, common humanity, and mindfulness, has been associated with resilience against the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It was also found that resilience and acceptance of HIV-positive status were enhanced after the exposure to CFT. In a different study, Skinta, Williams and Fekete (2019) determined that compassion-focused practices were significant in reducing HIV stigma and negative affect in PLWHA. Brion, participants' age differences as being a major confounding factor (Kamangar, 2012;Mousa, 2014).…”
Section: Cft and Newly Diagnosed Plwhamentioning
confidence: 99%
“…It was also found that resilience and acceptance of HIV-positive status were enhanced after the exposure to CFT. In a different study, Skinta, Williams and Fekete (2019) determined that compassion-focused practices were significant in reducing HIV stigma and negative affect in PLWHA. Brion, participants' age differences as being a major confounding factor (Kamangar, 2012;Mousa, 2014).…”
Section: Cft and Newly Diagnosed Plwhamentioning
confidence: 99%
“…A similar study ran moderated-mediations in a sample of HIV-positive diverse MSM. It was found that lower self-compassion moderated the indirect association between HIV-stigma and negative affect, through IH (Skinta et al, 2019). Specifically, the interactions between low self-compassion, HIV-stigma and IH were associated with greater negative affect; however, this was not the case for individuals reporting average or greater self-compassion.…”
Section: Risk Factors Among Hiv-positive Msmmentioning
confidence: 89%
“…HIV‐related stigma manifests at the individual (e.g., perceived, anticipated, and internalized) and interpersonal (e.g., enacted stigma) levels, and have produced stigma‐perpetuating policies (e.g., HIV criminalization; military and immigration bans) at state and national levels. Experiences of HIV‐related stigma across these levels have been associated with psychological distress, decreased social support, and poor HIV care continuum outcomes (Courtenay‐Quirk, Wolitski, Parsons, Gómez, & the Seropositive Urban Men's Study Team, ; Earnshaw, Smith, Chaudoir, Amico, & Copenhaver, ; Golub & Gamarel, ; Katz et al, ; C. Logie & Gadalla, ; Mahajan et al, ; Phillips et al, ; Quinn et al, ; Skinta, Fekete, & Williams, ).…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of HIV-related stigma across these levels have been associated with psychological distress, decreased social support, and poor HIV care continuum outcomes (Courtenay-Quirk, Wolitski, Parsons, Gómez, & the Seropositive Urban Men's Study Team, 2006;Earnshaw, Smith, Chaudoir, Amico, & Copenhaver, 2013;Golub & Gamarel, 2013;Katz et al, 2013;C. Logie & Gadalla, 2009;Mahajan et al, 2008;Phillips et al, 2011;Quinn et al, 2014;Skinta, Fekete, & Williams, 2018).…”
Section: Introductionmentioning
confidence: 99%